A Workplace Stretching Program for the Prevention of Musculoskeletal Disorders in Perioperative Staff: A Mixed-methods Implementation Study - King, Alison; Campbell, Joanne; James, Carole; Duff, Jed (Operating Room Nurses Association of Canada Journal, 2021)
Aim: The study aimed to investigate the acceptability, feasibility, use and impact of a workplace stretching program for preventing musculoskeletal disorders in perioperative staff. Method: This was a hybrid effectiveness–implementation study using mixed methods. Data was collected pre- and post-program to evaluate its impact on musculoskeletal disorders, discomfort, sick leave, incidents and compensation claims. A post-program survey and participant interviews were used to ascertain the programs acceptability, feasibility and use. Results: A total of 42 staff participated in the study. Following the program, there was a 60 per cent reduction in the odds of a musculoskeletal-related incident (OR 0.4, 95% CI 0.1, 8.0 p = 0.01) when compared with the rest of the hospital. The odds of a workers compensation claim reduced by 50 per cent (OR 0.5, 95% CI 0.1, 1.5, p = 0.8) and there was a 20 per cent decrease in the odds of a musculoskeletal disorder (OR 0.8, 95% CI 0.1, 7.0, p = 0.8) or sick leave (OR 0.8, 95% CI 0.1, 6.1, p = 0.8). There was no significant change in musculoskeletal discomfort scores preand post-program (+0.2, 95% CI -7.0, 7.3, p = 0.9). Greater than 70 per cent of participants felt that the program was acceptable and feasible with over 85 per cent agreeing that it was a good fit and matched department needs. Interviews with participants identified positive physical, psychological and cultural benefits. The most common shortcoming reported by staff was not having the opportunity to use the program enough. Conclusion: Given the positive results and the fact that the program requires minimal resources, it is recommended that other perioperative departments consider implementing a similar program to complement existing work health and safety initiatives.